Study of Knowledge of Hand Disinfection and Dental Impressions in Everyday Practice among Dental Students during a Pandemic by Coronavirus Disease 2019 - Stoeva, Velina; Bozhkova, Tanya; Atanasowski, Aleksandar; Kondeva, Veselina (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Dentistry is risky for acquiring and spreading a lot of infections. Patients in dental practice, especially those treated with dental prostheses, are at high risk both for acquisition and as a source of infectious diseases. AIM: Our study aims to estimate the level of knowledge about transmission of infections, hygienic disinfection of hands, and dental impressions among dental students during a pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/coronavirus disease 2019 (COVID-19). MATERIALS AND METHODS: An online anonymous survey was conducted among 106 students of dental medicine from the Faculty of Dental Medicine - Plovdiv, Bulgaria. RESULTS: According to 8.5% of students, hands are a factor for transmission of infections only if they are visibly contaminated and 2.8% do not think that hands are a factor. 19.3% believe that dental impressions could be a factor in transmitting microorganisms from the dentist to the dental technicians only if they are visibly contaminated and 1.8% deny this possibility. CONCLUSION: In our country, it is necessary to be done and implement in practice a protocol for disinfection of impressions and prostheses, as they are epidemiological factors for the transmission of microorganisms between the dental office and the dental laboratory. The results in practice, after the implementation of the protocol, should be checked regularly.